Achievement of ion temperatures in excess of 100 million degrees Kelvin in the compact high-field spherical tokamak ST40. (17th March 2023) - McNamara, S.A.M.; Asunta, O.; Bland, J.; Buxton, P.F.; Colgan, C.; Dnestrovskii, A.; Gemmell, M.; Gryaznevich, M.; Hoffman, D.; Janky, F.; Lister, J.B.; Lowe, H.F.; et al.
Abstract: Ion temperatures of over 100 million degrees Kelvin (8.6 keV) have been produced in the ST40 compact high-field spherical tokamak (ST). Ion temperatures in excess of 5 keV have not previously been reached in any ST and have only been obtained in much larger devices with substantially more plasma heating power. The corresponding fusion triple product is calculated to be n i 0 T i 0 τ E ≈ 6 ± 2 × 10 18 m − 3 keVs . These results demonstrate for the first time that ion temperatures relevant for commercial magnetic confinement fusion can be obtained in a compact high-field ST and bode well for fusion power plants based on the high-field ST.